Formation of XPhos‐Ligated Palladium(0) Complexes and Reactivity in Oxidative Additions. Issue 28 (26th April 2019) - Wagschal, Simon; Perego, Luca Alessandro; Simon, Alexandre; Franco‐Espejo, Aida; Tocqueville, Chanelle; Albaneze‐Walker, Jennifer; Jutand, Anny; Grimaud, Laurence
Abstract: Understanding the nature of the intermediate species operating within a palladium catalytic cycle is crucial for developing efficient cross‐coupling reactions. Even though the XPhos/Pd(OAc)2 catalytic system has found numerous applications, the nature of the active catalytic species remains elusive. A Pd 0 complex ligated to XPhos has been detected and characterized in situ for the first time using cyclic voltammetry and NMR techniques. In the presence of XPhos, Pd(OAc)2 initially associates with the ligand to form a complex in solution, which has been characterized as Pd II (OAc)2 (XPhos). This Pd II center is then reduced to the Pd 0 (XPhos)2 species by an intramolecular process. This study also sheds light on the formation of Pd I –Pd I dimers. Finally, a kinetic study probes a dissociative mechanism for the oxidative addition with aryl halides involving Pd 0 (XPhos) as the reactive species in equilibrium with the unreactive Pd 0 (XPhos)2 . Remarkably, the reportedly poorly reactive PhCl reacts at room temperature in the oxidative addition, which confirms the crucial role of the XPhos ligand in the activation of aryl chlorides. Abstract : A Pd 0 ligated to XPhos was detected for the first time and characterized in situ using cyclic voltammetry and NMR techniques. This study also evidenced the formation of a Pd I –Pd I dimer. Kinetic studies probe a dissociative mechanism for the oxidative addition with phenyl halides, including PhCl at room temperature.